Parafia Czerniewice – rok liturgiczny - Domańska, Aneta; Loba, Maciej (Zeszyty Wiejskie, 2017)
The parish of Czerniewice is one of the rural parish in Poland. The inhabitants of the parish from the generations cultivate religious traditions of the liturgical year. Common annual ecclesiastical celebrations unite and consolidate inhabitants. The annual custom and religious rite evolve, change, part of them decline and in their place appear new. Young people are interested in continuation of tradition, their religious life is not limited to participation in Holy Mass. Thanks to elder parishioners rites and customs, both local and ecclesiastical, are passed down from generation to generation, mainly in the form of active cultivation of the Christian traditions, does not disappeared and are still repeated in subsequent generations. Participation in the social, ecclesial community, belonging to a local organization, heavily integrates parishioners and allows them setting and implement common local goals and modern social media facilitate communications.